EXPLORING STRATEGIES FOR DEALING WITH DOMESTIC VIOLENCE FROM ISLAMIC LEGAL PERSPECTIVE - Ahmed, Ahmed Ramadan Mohamed; Zaghloul, Saad Gomaa Gomaa; Bakar, Marina Abu; Abous, Meryem (The journal of contemporary issues in business and government, 2021)
Domestic violence is one of the most common types of human violence prevalent since ancient times. Violence has increased in contemporary societies, its causes have varied, its forms and colours have varied, and its effects on our Islamic societies have begun to appear tangible. Domestic violence has become one of the most important contemporary family problems. Especially, with the increasing forms and types of increasing violence and the consequent adverse effects on the family and community stability. The Shariah has dealt with this violence that may cause the dissolution of the family and the disintegration of its foundations, so Islamic Shariah law has put in place the provisions and regulations that guarantee the protection, stability and survival of the family. Problem Statement: With the development of life and the emergence of various developments and contemporary issues, the issue of domestic violence between members of the same family has emerged on the social scene, which negatively affects the security and stability of society, which requires contemporary researchers and jurists to search for solutions to such problems that are exacerbated from time to time. Importance of Research: The importance of research appears as the family is the origin of the human community and on which the renaissance and progress of human nations are based, so Islam has been concerned with preserving it by developing strategies for interaction between members of the whole family. Research Objectives: The study aims to achieve the following goals: Explain the seriousness of domestic violence Means of eliminating domestic violence Strategies for dealing with domestic violence Research Questions What is meant by domestic violence? What is the danger of domestic violence? What are the strategies for dealing with domestic violence?